Macrolide Resistance in the Syphilis Spirochete, Treponema pallidum ssp. pallidum: Can We Also Expect Macrolide-Resistant Yaws Strains? - Šmajs, David; Paštěková, Lenka; Grillová, Linda (The American journal of tropical medicine and hygiene, 2015)
Treponema pallidum ssp. pallidum (TPA) causes over 10 million new cases of syphilis worldwide whereas T. pallidum ssp. pertenue (TPE), the causative agent of yaws, affects about 2.5 million people. Although penicillin remains the drug of choice in the treatment of syphilis, in penicillin-allergic patients, macrolides have been used in this indication since the 1950s. Failures of macrolides in syphilis treatment have been well documented in the literature and since 2000, there has been a dramatic increase in a number of clinical samples with macrolide-resistant TPA. Scarce data regarding the genetics of macrolide-resistant mutations in TPA suggest that although macrolide-resistance mutations have emerged independently several times, the increase in the proportion of TPA strains resistant to macrolides is mainly due to the spread of resistant strains, especially in developed countries. The emergence of macrolide resistance in TPA appears to require a two-step process including either A2058G or A2059G mutation in one copy of the 23S rRNA gene and a subsequent gene conversion unification of both rRNA genes. Given the enormous genetic similarity that was recently revealed between TPA and TPE strains, there is a low but reasonable risk of emergence and spread of macrolide-resistant yaws strains following azithromycin treatment.
Keywords: Treatment Failure; RNA, Ribosomal, 23S; mutace; neúspěšná terapie; Drug Resistance, Bacterial; antibakteriální látky; operon; Azithromycin; syfilis; RNA ribozomální 23S; Treponema pallidum; lidé; Anti-Bacterial Agents; Humans; bakteriální léková rezistence; Syphilis; Macrolides; Yaws; makrolidy; azithromycin; Mutation; frambézie; Operon